"Diseño de un sistema fotovoltaico conectado a la red eléctrica, para el laboratorio de prototipos de la carrera de ingeniería industrial de la Universidad Técnica Particular de Loja, en modalidad de autoconsumo" - Sarmiento Silva, Luis Miguel (2024)
The present research deals with grid-connected photovoltaic microgeneration in self-consumption mode, to promote the use of renewable energies and reduce its carbon footprint. The main objective is the development of a self-consumption photovoltaic power generation system that guarantees the self-supply of electric energy to the prototyping laboratory. The sizing of the SSFVCR followed the methodology of the “worst month method”, considering the month of June with a daily consumption of 43.03 kWh and a radiation of 3.59 kWh/m²/day, the inclination of the panels was set at 15° according to standardized tables. The main results show an estimated annual consumption of 1 266.06 kWh, which was ratified based on readings from a Fronius Smart Meter 65A-3 bidirectional energy meter, installed in July. As a result, a system design is presented, consisting of 33 modules arranged in 3 arrays and 11 strings, which will generate 13,513.83 kWh/year. On the other hand, the economic analysis estimated a return on investment in 9.94 years without inflation adjustments, a net present value (NPV) of 869.40 USD and an internal rate of return (IRR) of 8.86%, higher than the reference rate of the Central Bank of Ecuador of 8.23%. It is concluded that the design is financially viable and projects the energy sustainability of the laboratory. The design of the SSFVCR for the prototype laboratory of the industrial engineering career of the UTPL is a feasible and plausible solution, contributing to the university from the economic and educational point of view, as well as contributing to the reduction of climate change, reducing CO2 emissions. Keywords: Microgeneration, grid-connected photovoltaic system, economic feasibility, reduction in tCO2.